Pengaruh Lokasi, Kualitas Produk, Dan Store Atmosphere Terhadap Minat Beli Konsumen Ruang Luang Coffee Trenggalek - Yuliacipta, Annisa; Warsitasari, Wahyu Dwi (UIN Sayyid Ali Rahmatullah, 2023)
Abstract This research is motivated by several problems regarding the marketing strategy at coffee shops, including the number of existing coffee shops causing intense competition, product similarities, and similarity in store atmosphere presentation which raises high consumer buying interest in a coffee shop. Consumers who visit a coffee shop must think about the location, product quality and store atmosphere in the coffee shop they are going to go to. Of these three factors, it is a reference for consumers to visit a coffee shop. The purpose of this study is to determine the effect of location, product quality, and store atmosphere on consumer buying interest in Ruang Luang Coffee Trenggalek either simultaneously or partially. The method used in this study is a quantitative method and type of associative research. The population in this study was unknown consumers of Ruang Luang Coffee Trenggalek, therefore the researchers took 150 respondents who were considered sufficiently representative of the sample. Sampling using purposive sampling method with the criteria of respondents aged 17-56 years. The data analysis using multiple linear regression analysis. The results of this study are simultaneously location, product quality, and store atmosphere on consumer buying interest in Ruang Luang Coffee Trenggalek is a significant effect, while partially location, product quality and store atmosphere on consumer buying interest in Ruang Luang Coffee Trenggalek is a positive and significant effect